Gut microbiota-derived metabolites mediate the protective effects of Poria cocos polysaccharide derivatives against oxidative stress - Chunmin Yang; Fenfa Li; Pingping Yan; Xichun Peng (Food Bioscience, 2026)

Graphene quantum dots-bridged Fe-Ce bimetallic aerogel catalyst for efficient alkaline Fenton removal of three nitrogen species (NH3-N, NO3−-N, and NO2−-N) - Jie Li; Yuxiang Yang; Jining Zhang; Pingping Yao; Yan Huang; Anbang Dai (Environmental Research, 2026)

Climate-dependent nonlinear and interactive effects of the urban built environment on urban humid heat stress - Ziyan Zhou; Junhui Liang; Yan Yang; Zhenkun Wang; Pingping Tian; Haitao Wang (Sustainable Cities and Society, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

Fe-modified tea waste biochar enhances short-term soil organic carbon sequestration: Mechanisms and economic benefit - Weifeng Chen; Huiying Zhang; Yan Wang; Yun Xia; Pingping Lian; Hui Jia; Abdallah Abdelfattahe; Jinzhi Ni; Ran Wei (Environmental Research, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

Hydrological Effects Assessment of Double-Layer Permeable Pavement by Physical Experimental Basis - Pingping Luo; Yubin Zhang; Shiwen Zhu; Yixuan Zhang; Madhab Rijal; Peiyao Yan; Maochuan Hu (Water Resources Management, 2026)

Reshaping metal composition and sources to reduce PM2.5 oxidative potential by clean energy policies in Xi'an, China - Lijing Zhang; Pingping Liu; Hongyu Yan; Yuhao Dong; Shaozhong Guo; Hongmei Xu (Atmospheric Environment, 2026)

Investigation of the formation mechanism of mesophase pitch based on the evolution of molecular structure - Yan Yang; Qian Li; Pingping Zuo; Shijie Qu; Fangfang Qin; Wenzhong Shen (Fuel, 2026)

Hydrological response to climate change and urbanization in a semi-arid urban river - Jiqiang Lyu; Yan Wang; Kexin Wang; Wenya Liu; Dongyong Sun; Pingping Luo; Zhaohui Zhou; Meng Jiao; Aidi Huo; Peng Guo (Urban Climate, 2025)

Curcumin alleviates ovarian hyperstimulation syndrome in the rat model via inhibiting the nuclear factor kappa B/hypoxia-inducible factor-1α signaling pathway - Lilan Sun; Xiumei Zhuo; Dandan Qi; Hao Ma; Fanhua Kong; Pingping Sun; Yan Zhang; Peng Xue; Huagang Ma (Histochemistry and Cell Biology, 2025)

Characteristics and risk assessment of heavy metals and their acid-extractable fractions in atmospheric dustfall in urban and rural areas of Xi’an, China - Hao Zhang; Pingping Liu; Lijing Zhang; Shaozhong Guo; Hongyu Yan; Zhiwei Xue; Hongmei Xu; Zhenxing Shen (Air Quality, Atmosphere & Health, 2025)

Continuous and freeform manufacturing of hybrid laser-induced graphene and polyimide woven fabrics for enabling smart-textile garments with multifunctional wearable applications - Yajie Hu; Pingping Hao; Boru Du; Yan Gao; Weixiong Yang; Mingguang Han; Zhuang Hao; Haibin Duan; Xilun Ding; Sida Luo (Chemical Engineering Journal, 2025)

The coordination level of multi-actor environmental governance: marketization, technological innovation, and corruption - Yanhong Tang; Muzi Chi; Ruixue Yan; Weina Zhang; Yujing Zhao; Pingping Fu (Clean Technologies and Environmental Policy, 2025)

METTL14 knockdown augmented the polarization of M2-like macrophages to promote acute myeloid leukemia progression - Meng Wang; Zhibin Xie; Yuanyuan Tan; Yan Zhou; Siyi Wang; Pingping Zhang; Jiajia Li (Human Cell, 2025)

Single cell transcription revealing key transcription factors in embryonic kidney development - Jingxian Huang; Bing Yan; Hongwei Wu; Hougang Yang; Shaodong Luan; Haiyan Yu; Wei Shi; Pingping Ye; Fang Yuan; Qiang Yan; Fanna Liu; Lianghong Yin; et al. (Molecular and Cellular Biochemistry, 2025)

ATF4 regulates PI3K/AKT signaling axis to promote angiogenesis after myocardial infarction - Pingping He; Weirong Zeng; Jiao Li; Yu Zhang; Ranzun Zhao; Weiwei Liu; Yongchao Zhao; Zhijiang Liu; Changyin Shen; Wei Chen; Yan Wang; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2025)

Knock Off 3 SlNAIP Genes with Modified CRISPR-Cas9 Causes Dwarf Phenotype in Tomato - Jia Liu; Xinya Dan; Lili Wu; Pingping Fang; Yan Zhang; Xifeng Li; Yanfei Ding (Journal of Plant Biology, 2025)

Evaluation of pear orchard yield and water use efficiency at the field scale by assimilating remotely sensed LAI and SM into the WOFOST model - Liang Jiang; Feilong Zhang; Jianan Chi; Pingping Yan; Xiangxin Bu; Yong He; Tiecheng Bai (Computers and Electronics in Agriculture, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Corrigendum to “Complete biosynthesis of the potential medicine icaritin by engineered Saccharomyces cerevisiae and Escherichia coli” [Sci. Bull. 66(18) (2021) 1906–1916] - Pingping Wang; Chaojing Li; Xiaodong Li; Wenjun Huang; Yan Wang; Jiali Wang; Yanjun Zhang; Xiaoman Yang; Xing Yan; Ying Wang; Zhihua Zhou (Science Bulletin, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Effects of land consolidation intensity on landscape pattern and biodiversity in paddy ecosystem - Pingping Yang; Minzhu Shen; Yan Zhang; Hao Wang; Yinghao Xue; Baoxiong Chen; Jingjun Bian; Pengyao Li; Ti Zhang; Luyu Wang; Meichun Duan (Agriculture, Ecosystems & Environment, 2025)

Trees show higher resilience than herbs under phosphorus deficit induced by 12‐year simulated acid rain - Guangcan Yu; Mianhai Zheng; Ying‐Ping Wang; Mengxiao Yu; Jun Jiang; Enqing Hou; Nannan Cao; Shu Ye; Songjia Chen; Jingtao Wu; Fengcai Liu; Linhua Wang; et al. (Ecology, 2025)
Acid rain, with 60% deposition in Asia, may exacerbate plant phosphorus (P) limitation; however, its long‐term effects on different plant life‐forms remain largely undetermined. Understanding these effects is essential for predicting ecosystem resilience and promoting forest health under environmental change. Herein, we investigated the P status in two tree and two herb species and their rhizosphere soils after 12 years of acid treatment at three pH levels (pH: 4.0, 3.5, and 3.0) in a tropical forest in Southern China. We found that leaf, litter, and root P; leaf N and P resorption efficiency; and their ratios remained stable in trees; however, herb leaf and litter P levels declined. Acid addition reduced inorganic P in tree rhizosphere soil and inorganic and organic P in herb rhizosphere soil. Rhizosphere soil P fractions were more regulated by soil physicochemical properties and less regulated by microbial community in trees than in herbs. Under long‐term simulated acid rain, stable tree P status benefited from soil inorganic P depletion, and herbs partially met their P requirements via biological mineralization of soil organic P. These distinct P‐associated responses and acquisition strategies provide insights into safeguarding forest health among plants of different functional types under long‐term acid rain events.

Carboxylated celluloses as effective stabilizers for super-stable Pickering emulsions: Effects of different carboxyl moieties and particle morphologies on performance - Xiaoyun Chen; Feifan Zhang; Qiaomei Yang; Rusen Zhou; Yan Xu; Pingping Gao; Yadong Zhao (Food Hydrocolloids, 2025)

Degradation of TeCG catalyzed by graphene quantum Dot-reconstituted magnetic hydrotalcite composites - Yan Huang; Guangda Mu; Weiwei Huan; Yuxiang Yang; Hongmin Yuan; Irum Batool; Pingping Yao; Chengyin Wang; Xiangnong Liu; Chaoying Ni (Chemical Engineering Journal, 2025)

Controlled oxidative decomposition of rice husk to induce formation of hierarchically meso-macroporous carbon foams with unprecedented porosity - Hao Wu; Jun Yang; Ge Yang; Pingping Wu; Wei Xing; Peng Bai; Zifeng Yan (Biomass and Bioenergy, 2025)

Enterovibrio qingdaonensis sp. nov. and Enterovibrio gelatinilyticus sp. nov., two marine bacteria isolated from surface seawater of Qingdao offshore - Keyi Huang; Yi Liu; Yan Wang; Pingping Zhang; Haojin Cheng; Jinfeng Wang; Wanjia Tong; Wang Xiaolei; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2025)

Spectral Analysis of Dissolved Organic Carbon in Seawater by Combined Absorption and Fluorescence Technology - Xuan Cao; Feng Xiong; Yang Wang; Haikuan Ma; Yanmin Zhang; Yan Liu; Xiangfeng Kong; Jingru Wang; Qian Shi; Pingping Fan; Yunzhou Li; Ning Wu (Journal of Marine Science and Engineering, 2024)
Dissolved organic carbon refers to soluble carbon substances in water bodies and can be used as an important indicator for water pollution. Spectroscopic detection is commonly used to detect dissolved organic carbon in seawater. However, independent spectral methods are susceptible to interference, and insufficient extraction of the data features can occur. Accordingly, this study introduces a multisource spectral fusion method that relies on a combination of principal component analysis and convolutional neural networks to construct the detection model. The Bayesian correction method is used for calibration, and the dissolved organic carbon content of 10 groups of unfiltered seawater samples is analyzed. Correcting the spectral data acquired from samples containing impurities significantly improved the linear correlation coefficient R2 of dissolved organic carbon from 0.8891 to 0.9838. Similarly, the mean absolute error was significantly reduced from 15.33% to 3.24%, while the individual absolute error was effectively controlled, remaining within 9%. The obtained results show that the developed method effectively integrates the ultraviolet absorption and fluorescence spectral data and overcomes interference from other substances using the Bayesian correction method. Overall, this provides a highly accurate detection system with potential applications in monitoring the marine environment.

Independent induction of calluses and nematophytes from exfronds and their potential application for kelp cultivation and germplasm conservation - Pingping Tian; Weiwei Wang; Yan Li; Guangjin Liang; Juan Sun; Yanling Liu; Guanpin Yang; Xiaojie Li (Journal of Applied Phycology, 2024)

Alumina lattice confined Niσ+ species as highly selective and anti-coking sites for sustainable propane dehydrogenation - Peng Bai; Zhenxiang Zhao; Tian Nan; Jun Yang; Yantao Xue; Chunlin Wang; Shuanghui Lu; Hao Wu; Guoming Wang; Ziyi Zhong; Pingping Wu; Chunzheng Wang; et al. (Chemical Engineering Journal, 2024)

PM10 exposure induces bronchial hyperresponsiveness by upreguating acetylcholine muscarinic 3 receptor - Xue Xiao; Yali Lei; Tong Yao; Tingting Huang; Pingping Yan; Lei Cao; Yongxiao Cao (Toxicology and Applied Pharmacology, 2024)

Coastal conversion alters topsoil carbon, nitrogen and phosphorus stocks and stoichiometric balances in subtropical coastal wetlands - Minjie Hu; Jingtao Wang; Jordi Sardans; Hui Wu; Ranxu Ni; Pingping Guo; Ruibing Yan; Haoyu Liao; Chunya Liu; Josep Peñuelas; Chuan Tong (Science of The Total Environment, 2024)

Unravelling the structure-performance relationship of zeolite Beta in the catalytic cracking of low-density polyethylene by proposing gasoline factor as the descriptor - Yi Wang; Hao Wu; Yuanhao Liu; Wansheng Wang; Pingping Wu; Hongchao Fan; Zhihui Liu; Peng Bai; Zifeng Yan (Fuel, 2024)

A novel local grey model considering fluctuation based on kernel function for energy production prediction - Kailing Li; Pingping Xiong; Xinyan Huang; Yan Dong (Journal of Cleaner Production, 2024)

Analyte-perturbed balance between reducibility and fluorescence of Ti3C2 MXene quantum dots for label-free, dual-mode detection of silver ions - Peng Jin; Pingping Wan; Chunyan Zhang; Xu Li; Yan Wang; Jianxin Luo; Kun Li (Analytica Chimica Acta, 2024)

N-nitrosodimethylamine exposure to zebrafish embryos/larvae causes cardiac and spinal developmental toxicity - Xiaoyi Liu; Jinge Song; Xiaotao Yan; Pingping Li; Jinhua Zhang; Bin Wang; Jing Si; Yong Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Optimizing soil carbon content prediction performance by multi-band feature fusion based on visible near-infrared spectroscopy - Xueying Li; Pingping Fan; Huimin Qiu; Yan Liu (Journal of Soils and Sediments, 2024)

Historical and comparative overview of sponge campus construction and future challenges - Pingping Luo; Peiyao Yan; Xiaohui Wang; Yang Wu; Jiqiang Lyu; Bin He; Weili Duan; Shuangtao Wang; Xianbao Zha (Science of The Total Environment, 2024)

Effects of dietary supplementation with Radix Isatidis polysaccharide on egg quality, immune function, and intestinal health in hens - Panpan Shi; Zenghao Yan; Miaofen Chen; Pingping Li; Deqin Wang; Junjuan Zhou; Zhaojie Wang; Shihao Yang; Zhikun Zhang; Chuyuan Li; Yulong Yin; Peng Huang (Research in Veterinary Science, 2024)

Bibliometric evaluation of global research on eco-tourism - Han Lin; Yan Zhu; Zhoubao Sun; Pingping Wu; Jinjin Zhang (Environment, Development and Sustainability, 2023)

Dissecting the genetic basis of grain weight and size in common oat by genome-wide association study - Honghai Yan; Di Deng; Pingping Zhou; Yun Peng; Xiaolong Dong; Shuchang Li; Yongjie Zhang; Qin Man; Ziqin Lv; Tao Chen; Changzhong Ren; Yuanying Peng (Journal of Cereal Science, 2023)

Distribution and Controlling Factors of Dissolved Gaseous Mercury and Reactive Mercury in Seawater Near Yangtze River Estuary - Pingping Yin; Wen Zheng; Yan Wang; Ruhai Liu; Xin He; Haolin Sun; Dou Li (Journal of Ocean University of China, 2023)

Mediating and spatial spillover effects of public participation in environmental pollution governance mediated via traditional and new media - Pingping Ma; Yan Song; Ming Zhang (Journal of Environmental Management, 2023)

How does environmental tax affect enterprises’ total factor productivity? Evidence from the reform of environmental fee-to-tax in China - Longke Wang; Pingping Ma; Yan Song; Ming Zhang (Journal of Cleaner Production, 2023)

Plant above-ground biomass and litter quality drive soil microbial metabolic limitations during vegetation restoration of subtropical forests - Shuo Zhang; Ying-Ping Wang; Xi Fang; Jinlei Chen; Nannan Cao; Pingping Xu; Mengxiao Yu; Xin Xiong; Xiangping Tan; Qi Deng; Junhua Yan (Soil Ecology Letters, 2023)

Collagens for surimi gel fortification: Type-dependent effects and the difference between type I and type II - Yadong Zhao; Kunyu Lu; Xinyue Piao; Yan Song; Libin Wang; Rusen Zhou; Pingping Gao; Heng Yen Khong (Food Chemistry, 2023)

Prediction of zebrafish embryonic developmental toxicity by integrating omics with adverse outcome pathway - Xiao Gou; Cong Ma; Huimin Ji; Lu Yan; Pingping Wang; Zhihao Wang; Yishan Lin; Nivedita Chatterjee; Hongxia Yu; Xiaowei Zhang (Journal of Hazardous Materials, 2023)

Speciation and source changes of atmospheric arsenic in Qingdao from 2016 to 2020 - Response to control policies in China - Haolin Sun; Yan Wang; Ruhai Liu; Pingping Yin; Dou Li; Long Shao (Chemosphere, 2023)

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

rtcisE2F promotes the self-renewal and metastasis of liver tumor-initiating cells via N6-methyladenosine-dependent E2F3/E2F6 mRNA stability - Zhenzhen Chen; Lan Huang; Kaili Wang; Lulu Zhang; Xiang Zhong; Zhongyi Yan; Benyu Liu; Pingping Zhu (Science China Life Sciences, 2022)

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Causal associations of waist circumference and waist-to-hip ratio with type II diabetes mellitus: new evidence from Mendelian randomization - Kexin Li; Tianyu Feng; Lijuan Wang; Yang Chen; Pingping Zheng; Pan Pan; Min Wang; Isaac T. S. Binnay; Yingshuang Wang; Ruiyu Chai; Siyu Liu; Bo Li; et al. (Molecular Genetics and Genomics, 2021)

Dietary exposure to fatty acid esters of monochloropropanediols and glycidol of 2- to 3-year-old children attending nursery schools from two areas in China using the duplicate-diet collection method - Liang Jiang; Zhou Jing; Wang Yibaina; Song Yan; Xu Lili; Zhong Yanxu; Yong Ling; Zhou Pingping; Sui Haixia; Zhang Lei (Food Additives & Contaminants: Part A, 2021)

Genetic diversity and genome-wide association analysis in Chinese hulless oat germplasm - Honghai Yan; Pingping Zhou; Yun Peng; Wubishet A. Bekele; Changzhong Ren; Nicholas A. Tinker; Yuanying Peng (Theoretical and Applied Genetics, 2020)

Methylomonas rhizoryzae sp. nov., a type I methanotroph isolated from the rhizosphere soil of rice - Pingping Zhu; Minggen Cheng; Dongmei Pei; Yongchuang Liu; Xin Yan (Antonie van Leeuwenhoek, 2020)

Early Cretaceous volcanic and sub-volcanic rocks in the Erlian Basin and adjacent areas, Northeast China: new geochemistry, geochronology and zircon Hf isotope constraints on petrogenesis and tectonic setting - Jianzhou Tang; Zhicheng Zhang; Zejia Ji; Yan Chen; Ke Li; Yang Jinfu; Pingping Liu (International Geology Review, 2019)

Formulation and In Vitro Release Kinetics of Mucoadhesive Blend Gels Containing Matrine for Buccal Administration - Xiaojin Chen; Jun Yan; Shuying Yu; Pingping Wang (AAPS PharmSciTech, 2018)

Colon-Targeted Delivery of IgY Against Clostridium difficile Toxin A and B by Encapsulation in Chitosan-Ca Pectinate Microbeads - Pingping Xing; Yanan Shi; Chuangchuang Dong; Hong Liu; Yan Cheng; Junbo Sun; Dalei Li; Min Li; Kaoxiang Sun; Dongxiao Feng (AAPS PharmSciTech, 2017)

A Fluoro-Chromogenic Sensor Based on Organic Molecular Framework for Cu2+ and F− in Aqueous Soluble DMSO - Veikko Uahengo; Yan Zhang; Bi Xiong; Pingping Zhao; Ping Cai; Lydia Rhyman; Ponnadurai Ramasami; Kai Hu; Gongzhen Cheng (Journal of Fluorescence, 2017)

Direct cloning and transplanting of large DNA fragments from Escherichia coli chromosome - Ying Zhu; Yan Yang; Pingping Den; Yong Huang; Mengxiang Ni; Hongqing Fang (Science China Life Sciences, 2016)
We applied a resistance split-fusion strategy to increase the in vivo direct cloning efficiency mediated by Red recombination. The cat cassette was divided into two parts: cma (which has a homologous sequence with cmb ) and cmb , each of which has no resistance separately unless the two parts are fused together. The cmb sequence was integrated into one flank of a target cloning region in the chromosome, and a linear vector containing the cma sequence was electroporated into the cells to directly capture the target region. Based on this strategy, we successfully cloned an approximately 48 kb DNA fragment from the E. coli DH1-Z chromosome with a positive frequency of approximately 80%. Combined with double-strand breakage-stimulated homologous recombination, we applied this strategy to successfully replace the corresponding region of the E. coli DH36 chromosome and knock out four non-essential genomic regions in one step. This strategy could provide a powerful tool for the heterologous expression of microbial natural product biosynthetic pathways for genome assembly and for the functional study of DNA sequences dozens of kilobases in length.

Development of genic SSR markers from an assembled Saccharina japonica genome - Jie Peng; Linan Zhang; Xiaojie Li; Cuiju Cui; Ruina Wu; Pingping Tian; Yan Li; Yanling Liu (Journal of Applied Phycology, 2016)

A novel l-asparaginase from Aquabacterium sp. A7-Y with self-cleavage activation - Zhibin Sun; Ding Li; Pingping Liu; Wenhui Wang; Kai Ji; Yan Huang; Zhongli Cui (Antonie van Leeuwenhoek, 2016)

Effectiveness of first-line antiretroviral therapy in HIV/AIDS patients: A 5-year longitudinal evaluation in Fujian Province, Southeast China - Shouli Wu; Yuefeng Qiu; Pingping Yan; Wei Wang; Meirong Xie; Pincang Xia; Zhenghua Wang; Yansheng Yan (Archives of Virology, 2015)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

A single-loop recombinant pseudotyped-virus-based assay to detect HIV-1 phenotypic resistance - Shouli Wu; Pingping Yan; Yansheng Yan; Lijun Qiu; Meirong Xie (Archives of Virology, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Isolation and characterization of a proteinaceous α-amylase inhibitor AAI-CC5 from Streptomyces sp. CC5, and its gene cloning and expression - Zhibin Sun; Weihao Lu; Pingping Liu; Hui Wang; Yan Huang; Yuguo Zhao; Yi Kong; Zhongli Cui (Antonie van Leeuwenhoek, 2015)

Development of 27 trinucleotide microsatellite markers for Saccharina japonica using next generation sequencing technology - Linan Zhang; Jie Peng; Xiaojie Li; Yanling Liu; Cuiju Cui; Hao Wu; Ruina Wu; Pingping Tian; Yan Li (Conservation Genetics Resources, 2014)

An assessment of the surface climate in the NCEP climate forecast system reanalysis - Wanqiu Wang; Pingping Xie; Soo-Hyun Yoo; Yan Xue; Arun Kumar; Xingren Wu (Climate Dynamics, 2011)

Formation of melt pocket in mantle peridotite xenolith from western Qinling, Central China: Partial melting and metasomatism - Benxun Su; Hongfu Zhang; Patrick Asamoah Sakyi; Kezhang Qin; Pingping Liu; Jifeng Ying; Yanjie Tang; Sanjeewa P. K. Malaviarachchi; Yan Xiao; Xinmiao Zhao; Qian Mao; Yuguang Ma (Journal of Earth Science, 2010)

Isolation and characterization of 20 polymorphic microsatellite markers in Macrobrachium nipponense - Yan Zhao; Hui Wang; Xiangshan Ji; Yongqing Zeng; Pingping Yang; Lei Ding (Conservation Genetics Resources, 2010)

Some observations on harmful algal bloom (HAB) events along the coast of Guangdong, southern China in 1998 - Yuzao Qi; Jufang Chen; Zhaohui Wang; Ning Xu; Yan Wang; Pingping Shen; Songhui Lu; I.J. Hodgkiss (Hydrobiologia, 2004)